Effects of Rudder Position on the Ship Maneuvering - Wisnu Wardhana; Imam Rochani; Benedictus Johanes Belalawe (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2017)
The performance of the rudder on a ship affects the ability of the vessel to maneuver effectively. In the current study evaluation is made on the rudder mounted on a twin screw fast boat with LOA of 59.2 m and Vs of 28 knots. This paper discusses the forces acting on the rudder and the velocity distribution of the fluid flow due to the position of the rudder in 3 variations (X/L = 80%, X/L = 100%, X/L = 120%). The analysis undertaken in this study is based on CFD method. Analysis of the effectiveness of the maneuvers is performed by considering the magnitudes of the drag force and value of the lift force generated by the rudder, as well as a decrease in the fluid velocity u on the rudder area. On the variation of X/L = 120% with rudder angle 35°, the rudder produces a the largest value of total drag force and lift force, in the order of each 761 kN and 1,230 kN. The decrease of fluid velocity u most significantly also occurs in variation X/L = 120%, with a value of 10.0 m/s on the portside rudder and 9.3 m/s on the starboard rudder.